Administration of budget revenues - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the analysis of budget revenue administration. The correlation of the concepts «governmental management», «public management», «public administration» is investigated. It is established that public administration, becoming the basis of democratic achievements in the implementation of the executive and administrative functions of state bodies and local governments, has become widely used. Different views of scientistson the essence of the category of public administration are considered. Theoretical problems of budget revenue administration are investigated. A distinction is made between the concepts of «budget revenues» and «budget revenues». The classification of budget revenues by sections defined by the Budget Code is analyzed. It is substantiated that the planning, implementation, reporting and control and monitoring of budget revenues and current legislation should take place within a single mechanism of budget revenue management with the need to strengthen parliamentary control at all stages of the budget process.

Стаття присвячена аналізу адміністрування доходів бюджету. Досліджено співвідношення понять «урядове управління», «державне управління», «державне адміністрування». Встановлено, що державне управління, ставши основою демократичних досягнень у здійсненні виконавчо-розпорядчих функцій державних органів та органів місцевого самоврядування, набуло широкого застосування. Розглянуто різні погляди вчених на сутність категорії державного управління. Досліджено теоретичні проблеми адміністрування бюджетних доходів. Розрізняють подібні поняття «доходи бюджету». Проаналізовано класифікацію доходів бюджету за розділами, визначеними Бюджетним кодексом. Обґрунтовано, що планування, виконання, звітність, контроль та моніторинг надходжень до бюджету та чинного законодавства мають відбуватися в рамках єдиного механізму управління доходами бюджету з необхідністю посилення парламентського контролю на всіх етапах бюджетного процесу.
Latkovska T. A. Administration of budget revenues / T. A. Latkovska // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 214-231.
Keywords: budget process; budget revenue administration; public administration; classification of budget revenues; бюджетний процес; адміністрування доходів бюджету; державне управління; класифікація доходів бюджету; Research Subject Categories::LAW/JURISPRUDENCE::Public law